Concrete and reinforcement ratios for reinforced concrete buildings - Ong, Eng Hwee. (2009)
The objective of this study is to compare the amount of reinforcement and concrete used in the design of reinforced concrete buildings. The building categories included public residential projects, private residential projects, commercial projects and industrial projects. The issue on the design of public and private projects has generated great interest in the construction industry'. Many guidelines have been recommended by quantity surveyors to estimate and check the reinforcement ratio on the structural design of a building. However, few efforts have been made to numerically evaluate the reinforcement ratio.